Analisi Pengaruh JUB, Nilai Tukar, Suku Bunga Terhadap Inflasi Di Indonesia Periode 2018-2022 - Amir, Muhamad (Jurnal Ekonomika : INDEPENDEN, 2023)
Inflation is a continuous increase in prices over a certain period, and inflation is one of the impacts of the prolonged economic crisis that hit the country. Inflation is a condition where there is a sharp increase in prices that lasts continuously for a certain period of time. The purpose of this study is to analyze the effect of the money supply, interest rates, and exchange rates on inflation. The method used is a quantitative analysis tool with multiple regression using the Eviews method. Secondary data obtained by researchers from the results of publications conducted by the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results of the study show that the money supply and the exchange rate have no significant effect on the inflation rate, while the exchange rate has a significant effect on inflation..